Analisis Kesiapan Guru Sekolah Dasar dalam Mengimplementasikan Kurikulum Merdeka pada Pembelajaran - Dewi, Zaqia Rahma; Yanto, Anggel Hardi; Hanim, Muhammad Iqbal Jauhar (Universitas Nusantara PGRI Kediri, 2024)
The aim of this research is to describe and analyze the readiness of elementary school teachers in implementing the independent curriculum. This type of research is descriptive qualitative. Data collection was carried out by conducting direct interviews with 6 elementary school teachers regarding teacher readiness in implementing the independent curriculum. The research stages consist of 1) selecting a research topic, 2) literature study, 3) research focus, 4) data collection, 5) data processing, 6) data analysis, 7) conclusions and suggestions. The results of this research are that all teachers have a positive attitude towards implementing the independent curriculum policy by participating in training held by the government and participating in training independently. However, in terms of facilities and infrastructure, there are several schools that are unable to implement the independent curriculum because they are hampered by inadequate facilities.